Aglomerasi Industri dan Pengaruhnya terhadap Pertumbuhan Ekonomi Jawa Barat 2010-2014 - Annisa Kusumasari; Fitri Kartiasih (Jurnal Aplikasi Statistika & Komputasi Statistik, 2017)
Generally, economic growth of West Java has increased . However, the increase rates are different in each regions with one of the causes is the existence of economic concetration because of industrial agglomeration. This study analyze the phenomenon of industrial agglomeration and its effect to economic growth of West Java also the determinants of economic growth. Based on Cobb-Douglas function, fix effect model is used for spatial panel regression method that cover 26 regions in 5 years periods (2010-2014). Independent variables used are industrial agglomeration, infrastructure, human capital, capital, and labour with dependet variable is economic growth of West Java. The result shows that there are 8 regions that are agglomerated industrially. Meanwhile, human capital has the biggest elasticity. The characteristic of West Java’s economy is labour-intensive, with labour elasticity is higher than capital elasticity. Furthermore, infrastructure also has positive and significant influence to economic growth. In short, all of independent variables have positive and significant effect towards economic growth of West Java. Therefore, the enhancement of human quality and infrastructure must be improved so the economic growth can increase more.